Development and Testing of an Energy Storage Material/Phase Change Material Enhanced Heat Sink. Issue 17 (22nd November 2017) - Tu, Jianping; Shih, Wei; Mak, Henry; Yuen, Walter W.
ABSTRACT: A concept of using energy storage material (ESM) or phase change material (PCM) to enhance the heat transfer dissipation by a conventional compact fin-based heat sink is demonstrated. An actual design is developed, fabricated, and tested to demonstrate the heat transfer enhancement. The heat sink is light weight (made with Aluminum) and miniature in size with a total fin length of 26 mm. Test results demonstrated that under a high peak load (4.4 W/cm 2 ) and low duty power cycle (30/55 on/off ratio with a period of 85 sec), the peak temperature at the heating surface with the ESM/PCM heat sink is 5°C lower than that of a conventional heat sink. At the tip of the fin, the peak temperature with the ESM/PCM heat sink is 3°C lower than that of a conventional heat sink. When the external heat transfer coefficient increases (with increase air velocity), the impact of the PCM/ESM on the heat transfer performance is less. A numerical model, based on COMSOL, is developed to provide a theoretical understanding of the experimental observation.